Tradisi Pembuatan Lontong Tuyuhan di Kabupaten Rembang sebagai Sumber Pembelajaran IPA - Alvin Nur Zahro; Woro Sumarni; Cepi Kurniawan (Jurnal Penelitian Pendidikan IPA, 2023)
The aim of the research is to reconstruct the original science of the community into scientific science in the product of lontong tuyuhan located in Rembang Regency, Pancur District, Jeruk Village. The output of this research is the result of the reconstruction of the community's original science into scientific science in the product of lontong tuyuhan. This study uses a qualitative descriptive method through in-deepness interviews, firsthand observation, and documentation studies of making lontong tuyuhan. Data processing techniques include analysis, verification, reconstructing the community's original science into scientific science, and linking it with science learning competency standards. The results of this study are several concepts of indigenous knowledge of science in the manufacture of lontong tuyuhan which can be reconstructed into scientific science and integrated into science learning in schools, both senior high school, junior high school, and elementary school